(3UMjM GdHNGQjs - (3GdHNGQj, GdLYaj, CHh YHO Gddg, eMeO Hf ESeGYjd Hf EHQGgje, J (B256(3g`s
(3ChdgG (B:s
(3cJGH GdCTQHI hbhd Gddg JYGdi(B: {(3EfeG GdNeQ hGdejSQ hGdCfUGH hGdCRdGe QLS , GdBjI , MOKfG YHO Gddg Hf jhSas
(3BNQgG (B:s
(3GH bhd Gddg JYGdi(B: {(3hfVY GdehGRjf GdbSW djhe GdbjGeI(B} (3bGd GdfHj Udi Gddg Ydjg hSde(B: " (3cdeJGf MHjHJGf Edi GdQMef, NajaJGf Ydi GddSGf, KbjdJGf aj GdejRGf(B: (3SHMGf Gddg hHMeOg, SHMGf Gddg GdYXje (B"s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6 / 34s
(3eYLe GdeDdajf (B3 / 130s
(3cTa GdXfhf (B1 / 541s
(3TPQGJ GdPgH (B2 / 132s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK hGdeUWdMs